Characterization of centella asiatica (l.) Urban (pegaga) growth on different types of soil / Siti Halijah Hashim - Hashim, Siti Halijah (Faculty of Applied Sciences, 2015)
Centella asiatica or pegaga has a great potential value in pharmaceutical and nutraceutical industry. It is used worldwide since the ancient times in order to cure disease or to prevent illness. Thus, this study was done in order to provide much more information about Centella asiatica in term of morphology and its growth rate on different soil types. Three different soil types which are organic soil, sandy soil, and loam soil used as independent variables to study variation in growth traits as well as to know the suitable soil type for Centella asiatica growth. Plants were growing in laboratory for 10 weeks while its petiole length, number of leaves and fresh weight were measured. Besides, the morphological traits were observed during the whole weeks of this study. Plants growth shows an increasing in sandy soil and loam soil during week 1 until week 10. For organic soil, plant was died during week 4 because there is a microorganism infection on that soil. Centella asiatica can maximize growth and yield in sandy soil since it is show a higher measurement compared to loam soil.